Pancreatic Imaging A Pattern-Based Approach to Radiologic Diagnosis with Pathologic Correlation - Zaheer, Atif.; Fishman, Elliot K.; Pittman, Meredith E.; Hruban, Ralph H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This comprehensive teaching atlas covers virtually all pancreatic anatomy (including variants) and diseases in a pattern-based radiologic approach. Cases are presented as (3z(Bunknowns(3y(B, allowing the reader to analyze the findings and learn key points. Each teaching case includes a brief clinical history, images, a description of imaging findings, differential diagnoses, final diagnosis with images of gross pathology, and a discussion of key teaching points. The presented images have been acquired with the full range of relevant modalities, including state of the art technologies such as multidetector row dual-phase CT, 3D reformatting, and multiple MRI sequences. The book will help radiologists, radiology residents and fellows to sharpen their diagnostic skills by looking at a vast array of pathology from a major tertiary hospital (Johns Hopkins) and will also assist in preparation for radiology board examinations.s
Parenchymal abnormalities: Focal hypodense mass -- Diffuse Pancreatic hypodensity -- Cystic mass -- Solid hyperenhancing mass -- Gastrinoma -- Diffuse enlargement -- Ductal abnormalities -- Diffuse abnormalities -- Focal abnormalities.
Keywords: Medicine; Radiology; Endocrinology; Gastroenterology; Medicine & Public Health; Diagnostic Radiology; Gastroenterology; Endocrinology